2018
DOI: 10.1002/aoc.4309
|View full text |Cite
|
Sign up to set email alerts
|

Newly synthesized Cu(II) pyrazino[2,3‐f][1,10]phenanthroline complexes as potential anticancer candidates

Abstract: pyrazino[2,3-f][1,10]phenanthroline; gly: glycine;tyr: tyrosine), have been synthesized and characterized using CHN analysis, electrospray ionization mass spectrometry, Fourier transform infrared spectroscopy and single-crystal X-ray diffraction. Interaction of these complexes with calf thymus DNA has been investigated using absorption spectral titration, ethidium bromide and Hoechst 33258 displacement assay and thermal denaturation measurements. These complexes were found to be efficient cleaving agents and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 76 publications
1
5
0
Order By: Relevance
“…DMSO inhibition observed that the inhibition started at 50 μM DMSO concentration and higher in the complexes 1–3 + H 2 O 2 + DMSO systems. We suggest that the involvement of the hydroxyl radical in the cleavage pathway . A similar pathway was proposed by Sigman and co‐workers for the “chemical nuclease” activity of bis (phen) copper species …”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…DMSO inhibition observed that the inhibition started at 50 μM DMSO concentration and higher in the complexes 1–3 + H 2 O 2 + DMSO systems. We suggest that the involvement of the hydroxyl radical in the cleavage pathway . A similar pathway was proposed by Sigman and co‐workers for the “chemical nuclease” activity of bis (phen) copper species …”
Section: Resultssupporting
confidence: 83%
“…In this study stems from our continuous interest in defining and evaluating DNA/protein interactions of copper (II) complexes and also explore the relationship between structure and biological activity. Quite recently, we have reported the synthesis, characterization, DNA/protein interactions and biological activities of some binary and ternary copper (II) complexes . Additionally, we have investigated the stability constants of ternary complexes formed of copper (II) with substituted 1,10‐phenanthrolines and L‐amino acids in aqueous solution .…”
Section: Introductionmentioning
confidence: 99%
“…Due to this biological relevance, many copper(II) complexes have been synthesized and investigated for their biological activities . In our previously studies, we investigated anticancer, antimicrobial, antioxidant and antidiabetic activities and biomolecular interactions of copper(II) complexes of some 1,10‐phenanthroline derivatives and amino acids . And also we have investigated the stability constants of ternary complexes formed of copper(II) and palladium(II) with substituted 1,10‐phenanthrolines and amino acids in aqueous solution …”
Section: Introductionmentioning
confidence: 99%
“…[10,11] In our previously studies, we investigated anticancer, antimicrobial, antioxidant and antidiabetic activities and biomolecular interactions of copper(II) complexes of some 1,10-phenanthroline derivatives and amino acids. [12][13][14][15][16][17][18][19][20] And also we have investigated the stability constants of ternary complexes formed of copper(II) and palladium(II) with substituted 1,10-phenanthrolines and amino acids in aqueous solution. [21,22] In view of the above considerations, in the study reported here, our group focused on the synthesis and study of the properties of three copper complexes, namely {[Cu(phen)(trp)]ClO 4 ·3H 2 O} n (1), {[Cu(4-mphen)(trp)] SCHEME 1 Structures of ternary copper(II) complexes ClO 4 ·3H 2 O} n (2) and [[Cu(dmphen)(trp)(MeOH)] [Cu(dmphen)(trp)(NO 3 )]]NO 3 (3) (phen: 1,10phenanthroline; 4-mphen: 4-methyl-1,10-phenanthroline; dmphen: 4,7-dimethyl-1,10-phenanthroline; trp: L-tryptophan) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…19 1,10-Phenanthroline derivatives are one of the most unique N,O-containing ligands ascribing to rigid-exible combining structure. Researchers have also explored phenanthroline derivatives, such as pyrazine(2,3-f)- (1,10)phenanthroline, 20 2-(3-pyridyl)imidazo(4,5-f)-(1,10)phenanthroline 21,22 2-(2-carboxyphenyl) imidazo(4,5-f)- (1,10)phenanthroline (2-HNCP), 23,24 and 2-(4-carboxyphenyl)imidazo(4,5f)-(1,10)phenanthroline 25 and so on. Over the past several years, our group has been dedicated to the syntheses of some carboxyl derivatives of 1,10-phenanthroline to construct complexes and analysis of their luminescence and photocatalysis abilities on organic pollutants.…”
Section: Introductionmentioning
confidence: 99%